52.8k views
1 vote
Please! Solve f(x)-g(x) if f(x)=1/2x^4 - x^2 and g(x)= 3/4x^4 +3x^3 - x^2

User Darewreck
by
4.7k points

1 Answer

5 votes

Answer:


f(x)-g(x)=(-1)/(4)x^(4)-3x^(3)

Explanation:

This is a subtraction between polynomials, since both functions are polynomials, hence, to solve the problem with need to perform the subtraction, by coefficients.


f(x)= (1)/(2)x^(4)+0x^(3)-x^(2)\\\\g(x)=(3)/(4)x^(4)+3x^(3)-x^(2)

By performing the subtraction, we have:


f(x)-g(x)=(-1)/(4)x^(4)-3x^(3)

User Micawber
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.